Mengikuti Kristus: dari Kegelapan Menuju Cahaya Sejati (Yohanes 8:12) - Wara, Marselinus Mbabho Ora Wara (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2026)
This study aims to reveal the theological and spiritual meaning of Jesus’ declaration in John 8:12, “I am the light of the world; whoever follows Me will never walk in darkness.” The focus of this research is to understand the meaning of “following Christ” as a process of transformation from the darkness of sin to the light of salvation. Using a theological-biblical and hermeneutical approach of faith, this study interprets the Scripture contextually by considering its historical, theological, and existential meanings for the life of believers today. The results show that following Christ is not merely a religious act or verbal confession of faith, but a full participation in His life, love, and mission. The light of Christ is interpreted as a symbol of divine revelation that liberates humanity from sin and leads to a new life in love and truth. The theological reflection emphasizes that the light of Christ is personal, universal, and communal moving the Church and believers to be witnesses of love and bearers of light amid a world afflicted by moral and spiritual crises. This study underscores that following Christ means living an active faith and becoming a visible reflection of Christ’s light in daily life.